2017
DOI: 10.1007/s13204-017-0627-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of source parameters on the growth of metal nanoparticles by sputter-gas-aggregation

Abstract: We describe the production of size-selected manganese nanoclusters using a magnetron sputtering/aggregation source. Since nanoparticle production is sensitive to a range of overlapping operating parameters (in particular, the sputtering discharge power, the inert gas flow rates, and the aggregation length), we focus on a detailed map of the influence of each parameter on the average nanocluster size. In this way, it is possible to identify the main contribution of each parameter to the physical processes takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The experiments showed that the rate of the reflectance decrease is greater in the case of a relatively large pressure of argon in the vacuum chamber. The results obtained for the effect of argon pressure agree well with the data of Reference [19] on the important role of argon atmosphere in the formation of condensation nuclei. Note that the minimum value of relative reflectance observed at the final stage of copper melting is equal to R min n ≈ 0.04 for both values of argon pressure.…”
Section: The Decrease In Reflectance Of Molten Coppersupporting
confidence: 89%
“…The experiments showed that the rate of the reflectance decrease is greater in the case of a relatively large pressure of argon in the vacuum chamber. The results obtained for the effect of argon pressure agree well with the data of Reference [19] on the important role of argon atmosphere in the formation of condensation nuclei. Note that the minimum value of relative reflectance observed at the final stage of copper melting is equal to R min n ≈ 0.04 for both values of argon pressure.…”
Section: The Decrease In Reflectance Of Molten Coppersupporting
confidence: 89%
“…Interestingly, the mean particle size increases throughout the full range of the nanoparticle transit times and the evolution can be fitted to a single exponential relationship. This phenomenon suggests strongly that the increase in particle size is likely due to adatom condensation on the existing nanoparticle nuclei which is enhanced due to longer effective transit time 18 . We also see that the mass spectra are largely symmetrically distributed, closer to Gaussian than log-normal distribution, suggesting that the possibility of nanoparticle size increase through He-enhanced two-body collision of Pt nanoparticles is also small 19 .…”
Section: Resultsmentioning
confidence: 99%
“…An estimate provides a mean diameter of about 6.5 nm with a width of 1.3 nm, which is considerably monodisperse. It is well known that the presence of a low-molecular-weight gas during aggregation of the nanoparticles in the cluster source results in smaller sizes, as for example observed for manganese particles . Because the light molecules increase the gas flow, the transport of nanoclusters is promoted, leading to less aggregation time in the interior of the aggregation volume.…”
Section: Resultsmentioning
confidence: 99%